2019
DOI: 10.14716/ijtech.v10i3.2900
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mixed Biological Pretreatment and PEG 4000 on Reducing Sugar Production from Coffee Pulp Waste

Abstract: Biological methods using bacteria and fungi are regarded as more economically viable and environmentally friendly alternatives for improving lignocellulosic degradation. Coffee pulp waste (CPW) as a lignocellulosic biomass is abundant and has potential as a reducing sugar feedstock. However, it contains lignin as a matrix polymer, which associated with pectin and cover the cellulosic microfibrils and make it difficult to be digested during the bioprocess. In this study, the performance of biological pretreatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The ozone processing as pretreatment used to obstruct organic matter into biodegradable organic. This also happened in previous research, which stated that chemical or physical processes could not provide selective removal, they were expensive, and not environmentally friendly (Iswanto et al, 2019). Ozonation as a post-treatment after the MBBR processing aims to remove recalcitrant organic residues that cannot be degraded in the ozonation as a pre-treatment and the process of MBBR.…”
Section: Mbbr With Ozone Post-treatmentmentioning
confidence: 89%
“…The ozone processing as pretreatment used to obstruct organic matter into biodegradable organic. This also happened in previous research, which stated that chemical or physical processes could not provide selective removal, they were expensive, and not environmentally friendly (Iswanto et al, 2019). Ozonation as a post-treatment after the MBBR processing aims to remove recalcitrant organic residues that cannot be degraded in the ozonation as a pre-treatment and the process of MBBR.…”
Section: Mbbr With Ozone Post-treatmentmentioning
confidence: 89%
“…The use of coffee pulp as a substrate for phosphate solubilizing microorganisms (Cisneros-Rojas et al, 2016) [Kocuria sp, Bacillus subtilis (Cisneros-Rojas et al, 2017b) , (Cisneros-Rojas et al, 2017a) and S. diversispora, P. ochrochloron (Cisneros-Rojas et al, 2017a)] has also been studied; and has been reported to improve the availability of phosphorus for the development of coffee seedlings (Cisneros-Rojas et al, 2016, 2017a. Studies on the effects of Bacillus subtilis (BS), Aspergillus niger (AN), or Trichoderma reesei (TR), and PEG 4,000, have also been reported, with PEG 4000 showing better performance in reducing sugar production than the pulp waste alone (Iswanto et al, 2019a). Another surfactant, Tween 80, has shown improvements (Widjaja et al, 2019).…”
Section: Uses 21 Uses In Agriculturementioning
confidence: 99%
“…Coffee is undoubtedly one of the most popular drinks around the world, and for this reason, it has been widely studied (Mahachandra et al, 2017;Iswanto et al, 2019;Haryuni et al, 2019). Its commercialization occupies a very important place in the economies of countries like Colombia, Brazil, and Vietnam, among others.…”
Section: Introductionmentioning
confidence: 99%